Geometry Of Waves Guides For Containment Of Propagating Resonant Modes - Aboura, Z.; Bouhafs, B. (University of Eloued جامعة الوادي, 2011)
We are study de mode fundamental de 1D in the two media (MIM and IMI) of a metallic structure (Ag) (silver) in which a small hole is perforated (as à dielectric medium). We take the conditions that resonant modes (PPSs) are confined or the surface.Via the complex permittivity of the metal and those of the dielectric medium .The effective index neff of the elaborated structure controlled remarkably the properties of the propagating modes. Of the structure playing he mode to guide SPP modes .Where the confinement follow the order in sub-wave length scale of the width hole in silver and limited by the attenuation length (skin depth).
Articale in Journal of fundamental and Applied Sciences Vol. 03 N. 01
Keywords: metallic structure, effective index, guided SPP modes, skin depth.